A bibliometric analysis of exosomes in aging from 2007 to 2023 - Niu, Zenghui; Cui, Meiyu; Fu, Yingkun; Zhou, Lingfeng; Wang, Jiali; Lei, Yan; Fan, Xinrong; Wang, Qiang; Yang, Jing (Frontiers in Medicine, 2025)
Background Aging is the primary factor contributing to the development of aging-related diseases. As research on exosomes continues to advance, its relationship with aging and aging-related diseases has become a hot topic This article analyzes the research hotspots of exosomes in aging and aging-related diseases, aiming to fill the gap in bibliometric research in this field and help researchers better understand the current status and future trends of both fundamental and clinical research in this field. Methods The articles were retrieved and exported from WoSCC on December 18, 2023. The visual analysis of countries and regions, institutions, authors, references, and keywords in exosomes of aging was conducted using VOSviewer 1.6.18, CiteSpace 6.2.R7, and Bibliometrix. Results The bibliometric analysis included 1628 articles. China and the United States emerged as the top two leading countries in this field. A total of 2,321 research institutions from 78 countries and regions were primarily led by China and the United States. Both Kapogiannis D and Goetzl E were active authors in this field. Thery C, Valadi H, and Raposo G were the important promoters in this field. Thery C proposed the method of differential centrifugation and density gradient centrifugation to extract exosomes. Valadi H discovered cells could send RNA-messages to each other by loading them into exosome-vesicles. The journal with the highest number of articles was International Journal of Molecular Sciences, while PLoS One was the most frequently cited journal. The keyword analysis revealed that future research on exosomes in aging will possibly focus on “inflammation, cellular senescence, angiogenesis, insulin resistance, and Alzheimer's disease.” Conclusion We identified the research trends of exosomes in the field of aging through this bibliometric analysis. The present study provides valuable new perspectives on the history and current status of exosomes in the field of aging and aging-related diseases, and also offering guidance for future research directions.